2018
DOI: 10.1111/hsc.12700
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional survey of patients with open surgical wounds in Slovenia

Abstract: Most surgical wounds heal by primary intention, that is, the wound is closed with sutures, clips, or glue. However, some surgical wounds are either left open to heal from the bottom up (“healing by secondary intention”) or break open partially or fully after primary closure. There is little basic knowledge about the occurrence and natural history of surgical wounds healing by secondary intention (SWHSI); therefore, the aim of this survey was to estimate the number of people with SWHSI in Slovenia, the nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(72 reference statements)
1
3
0
2
Order By: Relevance
“…This study also found that females have lower rates of complex wounds in China than males, which is consistent with previous study conducted in China and Slovenia, 4,16,17 but different from the UK 1 10 -which showed that females are more likely to suffer from complex wounds. 30 The difference may be partially explained by differences in occupational and lifestyle activities with heavy labour and activities such as smoking being more common in older men than women of the same age.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study also found that females have lower rates of complex wounds in China than males, which is consistent with previous study conducted in China and Slovenia, 4,16,17 but different from the UK 1 10 -which showed that females are more likely to suffer from complex wounds. 30 The difference may be partially explained by differences in occupational and lifestyle activities with heavy labour and activities such as smoking being more common in older men than women of the same age.…”
Section: Discussionsupporting
confidence: 92%
“… 1 10 The same survey was carried out in Slovenia and found that the point prevalence of open surgical wounds was 0.38 ‰. 4 …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Pregled slovenske literature pokaže skope podatke o prevalenci kompleksnih ran, in sicer sta bili opravljeni dve obsežni prevalen ni študiji (Franks et al, 2007;Pađen et al, 2019) in dve študiji, ki bi ju bilo možno klasificirati kot neke vrste »klini no presojo zdravstvene prakse« (ang. clinical audit) oz.…”
Section: Razširjenost Kompleksnih Ranunclassified